Established and emerging new approach methodologies in neuroscience - Imberechts, Dorien; Ny, Annelii; Copmans, Daniëlle (Frontiers in Neuroscience, 2025)
The increasing need for ethical, human-relevant, and efficient alternatives to animal testing is driving the development of New Approach Methodologies (NAMs) in safety assessment and drug development. However, the inherent complexity of neurological diseases presents a significant challenge to fully replace animal models in this field. In neuroscience, a range of NAMs, from traditional 2D cell cultures to advanced brain organoids and alternative vertebrate models like zebrafish, demonstrate complementary strengths and limitations. Together, these models support translational research, including the investigation of neurodevelopment, disease, and neurotoxicity. While human and mouse brain organoids that mimic the structural and functional properties of mammalian brain tissue hold great promise, their applicability for high-throughput screening is hindered by their cost- and time-intensive nature. Complementary approaches such as embryonic and larval zebrafish models and the emerging zebrafish brain organoids provide faster, cost-effective, and scalable yet biologically relevant platforms for early-phase screening, thanks to the zebrafish’s rapid development, conserved vertebrate neuroanatomy, and proven value in toxicology. This review maps the current landscape of NAMs in neuroscience, examining approaches ranging from 2D and 3D in vitro systems to zebrafish models. It highlights the advantages and challenges of the different models, including a comparison of human, mouse, and zebrafish brain organoids, and outlines the future directions for integrating these complementary systems into robust, efficient, and ethically responsible pipelines for both early-phase toxicity testing and drug discovery.